Role of Digitalization: Why Game-Based Learning Important During the COVID-19 Pandemic? - Yoriska Noventi Putri; Achmad Lutfi; Harun Nasrudin (Indonesia Emerging Literacy Education, 2023)
Objective: Game-Based Learning (GBL) is an e-learning platform that drives learning. It can be used as an additional option for teachers because it integrates the learning process with the experience of playing games that can be done anywhere and anytime. The distance learning or online learning set by the government during the COVID-19 pandemic could not support learning. Obstacles faced by students resulted in a decrease in achievement due to the inaccuracy of the strategies and learning methods used by the teacher during the learning process. This study aimed to determine the role and usefulness of the GBL method during the pandemic. Method: The research method used is a qualitative literature review method with fifteen main articles as a reference. Result: The results of the study found that the role of GBL during the pandemic is to fun learning, increase interest in learning, increase student motivation, improving student learning outcomes, improving mastery of learning, improve student cognitive ability, increase student activity, boosting creativity, improve concept understanding & knowledge, practice digital literacy, and practice self-efficacy. Novelty: GBL method is essential and plays a significant role in learning during the pandemic. The advantage it has can be used to improve student achievement, primarily when online learning is implemented. However, in the process, parental supervision is still needed so students can avoid game addiction.